Autopercepção de competência profissional de estudantes estagiários de licenciatura em educação física sobre a educação especial - Gustavo Schiarolli; Nilton Munhoz Gomes; Jorge Both (Universidade Estadual do Oeste do Paraná, 2018)
The objective of the study was to analyze the self-perception of professional skills considering the social demographic variables of the Physical Education Degree students who had done Supervised Internship at Special Education. The descriptive and cross section study had a sample of 28 students who were matriculated at the subject Supervised Internship II offered at the 4th year of the Physical Education course in Londrina State University. The instrument for data collection was composed by a social demographic questionnaire and the Self-Perception of Professional Skills Scale in Physical Education and Sports. For statistical data analysis was used the t test and chi-square for one sample test. In the analysis was considered a significance level of 95% (p<0.05). The results showed that students had only a professional skill at the motivation skill. Also, the students who had previous experience with people with special necessities had more levels of self-perceived professional skill in the issues related to student discipline and planning activities. The students who did not have experiences with teaching felt much competent in disciplinary matters and pedagogical action, in the knowledge dimension and global evaluation of professional skill. Finally, the students who participated in teaching projects were more critics about the self-reflection indicator. It is concluded that student´s self-perception of professional skill was low, being the experience of living with special necessity persons which had a positive impact in the researched group, while the experience in teaching and participation in teaching projects helped with the emergence of critical sense about the self-perception of professional skill.